Absence of cardiac damage induced by long-term intensive endurance exercise training: A cardiac magnetic resonance and exercise echocardiography analysis in masters athletes - Olivier Missenard; Charline Gabaudan; Helene Astier; Florian Desmots; Eric Garnotel; Pierre-Laurent Massoure (Elsevier, 2021)
Objectives: It is under debate whether the long-term practice of intensive endurance exercise induces chronic cardiac damage such as myocardial fibrosis and ventricle contractile dysfunction. Multimodality analysis was performed to evaluate myocardial damage induced by long term intensive endurance training in master athletes. Methods: Thirty-three asymptomatic endurance master athletes (47 ± 6 year-old, 9,6 ± 1,7 h training/week for 26 ± 6 years), were compared to 18 sedentary controls (49 ± 7 year-old). They underwent a CMR protocol including 4 chambers morphological and late gadolinium-enhancement (LGE) analysis, left (LV) and right ventricular (RV) T1 mapping and calculation of cardiac extracellular volume (ECV). A maximal exercise echocardiography with left and right ventricular longitudinal global strain (LGS) analysis was performed. Cardiac biomarkers of fibrosis (high sensitive cardiac Troponin T, N-Terminal pro brain natriuretic peptide, N-terminal propeptide of procollagen type I and N-terminal propeptide of procollagen type III) were analysed. Results: Athletes had larger left and right atrial volume, LV and RV end diastolic volume and increased LV and RV mass compared to controls. LGE was not found in athletes. Native T1 values of LV and RV were not significantly different in athletes compared with controls. ECV was normal in both groups (21,5%± 1,6% [18.3 - 23%] in athletes, 22%± 2,2% [18.5 - 27%] in controls). LV and RV peak exercise LGS values were higher in athletes. Cardiac biomarkers levels were normal. Conclusion: Despite significant physiological cardiac remodelling, consistent with previous descriptions of athlete's heart, there was no evidence of myocardial fibrosis or exercise left or right ventricular dysfunction or cardiac fibrosis in endurance athletes. Our results are not supporting the hypothesis of deleterious cardiac effects induced by long term and intensive endurance exercise training.